Contemporary treatment options for a classical disease: Advanced Hodgkin lymphoma. (April 2020) - Reid, Justin H.; Marini, Bernard L.; Nachar, Victoria R.; Brown, Anna M.; Devata, Sumana; Perissinotti, Anthony J.
Graphical abstract: Abstract: Advanced classical Hodgkin lymphoma (cHL) is a rare lymphoid disease characterized by the presence of Hodgkin and Reed-Sternberg (HRS) cells. Each year, cHL accounts for 0.5% of all new cancer diagnoses and about 80% are diagnosed with advanced stage disease. Given the significant improvement in cure rates, the focus of treatment has shifted towards minimization of acute and long-term toxicities. PET-adapted strategies have largely been adopted as standard of care in the United States in an attempt to balance toxicities with adequate lymphoma control. However, the appropriate upfront chemotherapy regimen (ABVD versus eBEACOPP) remains controversial.